The Brazilian LGBT+ Health Survey: methodology and descriptive results - Juliana Lustosa Torres; Gabriela Persio Gonçalves; Adriana de Araújo Pinho; Maria Helena do Nascimento Souza (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
The understanding of health care demands and possible access barriers may support policymaking and best practices targeting the lesbian, gay, bisexual, transgender, and related identities (LGBT+) population. The aims of the Brazilian LGBT+ Health Survey were to characterize the LGBT+ population during the COVID-19 pandemic and to specify the characteristics of the COVID-19 pandemic in this population. This is a cross-sectional online study, with a convenience sample of 976 individuals identified as LGBT+, aged 18 years or older from Brazil. It allows investigations of sexuality, discrimination, internal homophobia, health-related behaviors, and health care access. The study adopts a conceptual framework (i.e., validated tools and measures) common to other epidemiological studies, allowing comparisons. We describe the study methodology, some descriptive results, and health-selected indicators compared with the Brazilian National Health Survey. Most of the respondents were from Southeast Region (80.2%), mean aged 31.3 (± 11.5 years). Regarding COVID-19, 4.8% tested positive. Both weekly episodes of discrimination (36%) and depression prevalence (24.8%) were high among the LGBT+ population in Brazil, highlighting mental health and homophobia as major concerns in the LGBT+ context during the pandemic. Although a decade has passed since the institution of the Brazilian National Policy for Comprehensive LGBT Health, appropriate training of health professionals to offer adequate services is still needed. Knowledge of the specific health demands of this group might guide person-centered best practices, promote sexual minority high-acceptance settings, and contribute to higher equity during the pandemic.